0205 Sleep Need: More Influential on Health and Daytime Function than Sleep Duration?. (25th May 2022) - Scott, Hannah; Appleton, Sarah; Reynolds, Amy; Gill, Tiffany; Melaku, Yohannes; Adams, Robert; Catcheside, Peter; Perlis, Michael
Abstract: Introduction: Most prior research into relationships between sleep and health and daytime functioning have focused on average sleep duration or efficiency and ignored individual differences in sleep need. This study tested if sleep need is more strongly correlated with self-rated health and daytime function than sleep duration. Methods: Data were drawn from the 2019 Sleep Health Foundation online survey of adult Australians (N=2, 044, aged 18-90 years). Hierarchical multiple regressions assessed variance explained (R2 and R2 change) by demographics (Model 1: age, sex, BMI), self-reported sleep duration (Model 2: Model 1 + weighted variable of typical weekday/weekend sleep duration), and individual sleep need (Model 3: Model 2+ rating on a 5-point scale to 'how often you get enough sleep to feel your best the next day') on daytime function items for fatigue, concentration, motivation, and overall self-rated health (visual-analog scale from 0-100). Results: Sleep need explained an additional 17.5–18.7% of the variance in fatigue, concentration, motivation, and health rating (all p < 0.001 for R2 change) in Model 3. In contrast, Model 2 showed that sleep duration alone only explained an additional 2.0–4.1% variance in these outcomes after accounting for demographic variables. Findings were similar when stratified by sex. Sleep need also explained greater variance for older adults than for younger and middle-aged adults, especially on health rating (Model 3: R2 change = 0.11 for ages 18-24y, 0.14 for 45-54y, 0.27 for 75y+). Conclusion: Sleep need appears to explain considerably more variance in daytime function and self-rated health than sleep duration. The effect of sleep need on other daytime consequences, and in clinical populations, needs further exploration. Validated assessments of sleep need are also needed to elucidate its importance for understanding the effect of sleep on health and functioning. Support (If Any): The 2019 Sleep Health Foundation online survey was supported by the not-for-profit Sleep Health Foundation using an unrestricted grant from Merck Sharp & Dohme (Australia) which did not inform nor restrict study design, methodology, or presentation.